Stomatal Crypts Have Small Effects on Transpiration: A Numerical Model Analysis - Roth-Nebelsick, Anita; Hassiotou, Foteini; Veneklaas, Erik J (Plant physiology (Bethesda), 2009)
Stomata arranged in crypts with trichomes are commonly considered to be adaptations to aridity due to the additional diffusion resistance associated with this arrangement; however, information on the effect of crypts on gas exchange, relative to stomata, is sparse. In this study, three-dimensional Finite Element models of encrypted stomata were generated using commercial Computational Fluid Dynamics software. The models were based on crypt and stomatal architectural characteristics of the species Banksia ilicifolia, examined microscopically, and variations thereof. In leaves with open or partially closed stomata, crypts reduced transpiration by less than 15% compared with nonencrypted, superficially positioned stomata. A larger effect of crypts was found only in models with unrealistically high stomatal conductances. Trichomes inside the crypt had virtually no influence on transpiration. Crypt conductance varied with stomatal conductance, boundary layer conductance, and ambient relative humidity, as these factors modified the three-dimensional diffusion patterns inside crypts. It was concluded that it is unlikely that the primary function of crypts and crypt trichomes is to reduce transpiration.